Higher-order QCD in the decay Higgs to two photons - Neves, Gabriel Augusto das (2021)
In the absence of direct observation of Physics Beyond Standard Model at the LHC, precise tests of the theory require increasing accuracy. The decay width of the Higgs boson into photons is known, incompletely, at the 5-loop level, i.e. N4LO in the strong coupling, α4s, while the exact knowledge of the QCD corrections is up to N2LO or the 3-loop level. In this work, we calculated, for the first time, the effect due to higher-order QCD corrections in the decay H → γγ through the so-called large-β0 limit, in which the corrections from the leading-nf terms are known to all orders in αs. The analysis of the series´ singularities in Borel space enable us to study, in a semi-qualitative way, the series behaviour with respect to variations of the renormalization scale. Furthermore, we calculated the Borel sum due to the contribution of the leading-nf diagrams, trying to understand the significance of the diagrams which are sub-leading in nf , and the optimal renormalization energy scale to compute the QCD corrections of Γ(H → γγ). Finally, we estimated the magnitude of the next QCD correction as well as the error due to truncation of the series with the known perturbative corrections in QCD.